Thickness Dependent Ultrafast Charge Transfer in BP/MoS2 Heterostructure. (31st August 2022) - Yin, Yanyu; Zhao, Xingju; Ren, Xiaoyan; Liu, Kun; Zhao, Jin; Zhang, Lili; Li, Shunfang
Abstract: Constructing high‐performance‐2D heterostructures and deciphering the underlying microscopic mechanism of carrier dynamics are crucial in optoelectronic and photovoltaic applications. Here, taking black phosphorus (BP)/MoS2 heterostructure with type‐II band alignment as a prototypical example, the ab initio nonadiabatic molecular dynamics simulations demonstrate that the interlayer carrier dynamics are thickness dependent. Specifically, the electron transfer from a monolayer (1L)‐BP to MoS2 occurs quickly within 54 fs. In contrast, hole transfer can only be observed within 1 ps with BP's layer number N ≥ 2, triggered by the excitation of low‐frequency acoustic phonon and interlayer shear and breathing phonon modes within 100 cm –1 that enhances the interlayer coupling. Particularly, the electron and hole transfer time exhibits respectively linear and exponential dependence on the layer number N of BP component. The present findings shed new light on improving the process of ultrafast carrier dynamics of 2D heterostructures for photoconversion. Abstract : Our results demonstrate that the electron transfer from a monolayer(1L)‐black phosphorus (BP) to MoS2 occurs quickly within 54 fs. In contrast, hole transfer can only be observed within 1 ps with BP's layer number N ≥ 2. Moreover, the electron and hole transfer time scales exhibit respectively linear and exponential dependence on the layer number N of BP component.